Recombinant rubella vectors elicit SIV Gag-specific T cell responses with cytotoxic potential in rhesus macaques - Rosati, Margherita (Vaccine, 2015)
Live-attenuated rubella vaccine strain RA27/3 has been demonstrated to be safe and immunogenic in millions of children. The vaccine strain was used to insert SIV gag sequences and the resulting rubella vectors were tested in rhesus macaques alone and together with SIV gag DNA in different vaccine prime-boost combinations. We previously reported that such rubella vectors induce robust and durable SIV-specific humoral immune responses in macaques. Here, we report that recombinant rubella vectors elicit robust de novo SIV-specific cellular immune responses detectable for >10 months even after a single vaccination. The antigen-specific responses induced by the rubella vector include central and effector memory CD4(+) and CD8(+) T cells with cytotoxic potential. Rubella vectors can be administered repeatedly even after vaccination with the rubella vaccine strain RA27/3. Vaccine regimens including rubella vector and SIV gag DNA in different prime-boost combinations resulted in robust long-lasting cellular responses with significant increase of cellular responses upon boost. Rubella vectors provide a potent platform for inducing HIV-specific immunity that can be combined with DNA in a prime-boost regimen to elicit durable cellular immunity.